THE EFFECT OF LIQUID ORGANIC FERTILIZER CONCENTRATION OF GOAT MANURE ON THE GROWTH AND YIELD OF CHERRY TOMATOES ON PEAT SOILS - Fauzan, Rizki; ., Nurjani; ., Maulidi (Jurnal Sains Mahasiswa Pertanian, 2020)
This study aims to determine the effect of liquid organic fertilizer of goat manureon the growth and yield of cherry tomatoes on peat soil. The research was conducted fromJanuary 13th 2019 to April 21th2019 in the garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The study used a completely randomized design (CRD) method in which the application of liquid organic fertilizer concentration as a single factor. The treatments were designed in five levelsof concentrationwith 5 replications and 4 sample plants. The treatment were 10%, 20%, 30%, 40%, 50%. The variables observed in this study were plant height, root volume, root dry weight, of the plant dry weight, plant dry weight, amount of fruit crops, weight of fruit crops, weight of fruit. Based on the results of the study, it can be concluded that giving various concentrations of liquid organic fertilizer of goat manurecannot increase growth, but can inrease cherry tomato yield on peat soils. Giving liquid organic fertilizer goat manure with concentration 20% indicates the effective concentration for cherry tomato plants on peat soils.Â Keywords: cheryy tomatoes, goat manure, liquid organic fertilizer,peat soils